2020
DOI: 10.1186/s12891-020-03534-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study on trajectories and prognostic factors of mid back pain

Abstract: Background: Although mid back pain (MBP) is a common condition that causes significant disability, it has received little attention in research and knowledge about trajectories and prognosis of MBP is limited. The purpose of this study was to identify trajectories of MBP and baseline risk factors for an unfavorable outcome in MBP patients undergoing chiropractic treatment. Methods: This prospective-observational study analyzes outcome data of 90 adult MBP patients (mean age = 37.0 ± 14.6 years; 49 females) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Knecht et al investigated the various trajectories of mid-back pain and baseline risk factors for unfavorable outcomes for patients undergoing chiropractic treatment. Their results found that pain that lasts for more than 3 months before a treatment is associated with poor outcomes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knecht et al investigated the various trajectories of mid-back pain and baseline risk factors for unfavorable outcomes for patients undergoing chiropractic treatment. Their results found that pain that lasts for more than 3 months before a treatment is associated with poor outcomes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified clusters of pain trajectories among individuals living with chronic pain. Some have focused on participants with 1 chronic pain condition, such as osteoarthritis [ 15 , 36 - 39 , 52 - 58 ], low back pain [ 13 , 14 , 27 , 59 - 65 ], other back pain [ 25 , 32 , 49 , 66 ], neck or shoulder pain [ 33 , 61 , 67 , 68 ], leg pain [ 29 ], knee pain [ 69 ], or foot pain [ 70 ], whereas others have identified clusters among a broader population, such as those with musculoskeletal pain [ 26 , 31 , 47 , 71 , 72 ] or general pain [ 48 , 73 - 75 ]. Clusters in these studies were described by the severity of pain (eg, no pain , very low pain , mild pain , moderate pain , high pain , and severe pain ), the level of change in pain severity (eg, persistent , ongoing , episodic , worsening , recovering , and fluctuating ), or a combination of these features.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, some previous studies have used methods from the k-means and k-medoids family of algorithms. Knecht et al [ 25 ] used the KmL package to identify 2 clusters in responders and nonresponders groups. Weng et al [ 76 ] used a k-median algorithm to identify 4 clusters of pain severity: slightly rise , completely drop , sudden rise , and steady group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that most patients display an initial attenuation in symptoms and disability subsequent to the onset of an acute episode of spinal pain (Burns et al, 2020;Carroll et al, 2008;Vasseljen et al, 2013;Vos et al, 2008). Although this initial improvement is also found in patients already in a long-lasting course of pain, it seems to be larger and more rapid in patients presenting at the onset of an acute episode (Bot et al, 2005;Knecht et al, 2020;Langenfeld et al, 2015;Leaver et al, 2013;Peterson et al, 2012;Rubinstein et al, 2008). Previous research is mainly based on outcomes measured as mean values at single time points.…”
Section: Introductionmentioning
confidence: 99%